Synthesis of central spiro-bis-THF fragments of symbiospirols A-C - Shinde, Mahesh H.; Kona, Chandrababu N.; Ramana, V. Chepuri (New Journal of Chemistry, 2022)
The gold catalysed alkynediol spiroketalization to assemble the central spiro-bis-THF fragments (C22-C33 and C36-C47) of symbiospirols A-C is documented. The adopted chiral pool approach employed commercially available d-glucose and l-malic acid in the synthesis of key building blocks. In addition, two other possible diastereomers have been synthesized in order to establish the relative stereochemistry of the unassigned THF-center of symbiospirols B/C.